Reconfiguring Religion in The Digital Era: A Conceptual Framework for The Mediatization of Religion in Indonesia - Effendi, Erus; Waliyajati, Roro Sri Rejeki; Truna, Dody S. (Abrahamic Religions: Jurnal Studi Agama-Agama, 2026)
This article examines how religion is reconfigured in the era of digital platforms and proposes a conceptual framework for the mediatization of religion in Indonesia. While existing scholarship on digital religion has provided rich empirical insights, much of it remains fragmented and often limited to specific platforms or practices. This study addresses that limitation by reconstructing the multidimensional framework of Rodrigues and Harding and integrating it with mediatization theory, the phenomenology of religion, and digital religion scholarship. The study employs a conceptual and analytical approach based on a focused literature review and theoretical synthesis. The analysis produces a framework organized around five interrelated components: media logic, algorithmic curation, networked community, authority shift, and ethical governance. Building on this framework, the article advances three conceptual propositions concerning algorithmic shifts in authority, the transformation of sacred experience under digital mediation, and the expansion of epistemic participation alongside its associated risks. To demonstrate the analytical capacity of the framework, the article draws on literature-based illustrations of the digital hijrah movement and online pengajian in Indonesia. These cases show how digital infrastructures reshape authority, ritual practice, and community formation while also generating tensions related to fragmentation, polarization, and misinformation.